Exploiting phase separation in monolithic La0.6Ca 0.4MnO3 devices - Granja, Leticia Paula (2013)
Devices based on mesas were fabricated from thin films of magnetically phase-separated La0.6Ca0.4MnO3. Low-field magnetoresistance arises because the volume fraction of the ferromagnetic metallic phase is large enough for percolation but small enough to permit magnetic decoupling between each mesa and the underlying track. Magnetic domain walls in the antiparallel mesa-track configuration possess a giant resistance-area product of (3-7) × 10-8 Ωm2. This figure represents an 11 order-of-magnitude improvement with respect to the figure for cobalt.